Evaluation of the hematological parameters, inflammatory biomarkers, and thyroid hormones in hypothyroidism patients - Marzieh Haghbin; Fatemeh Razmjooei; Fatemeh Abbasi; Roxana Rouhie; Parisa Pourabbas; Hamed Mir; Abazar Roustazadeh; Mirza Ali Mofazzal Jahromi; Kambiz Bagheri (BMC Research Notes)
Abstract Aim Hypothyroidism is created by disruption of thyroid hormone production, which can destroy the emotional, relational, social, and working life of patients if left untreated. Hypothyroidism has multiple etiologies. We evaluated the relationship of hematological parameters and inflammatory biomarkers with thyroid hormones to find the potential use of these items in patients screening and prognosis. Methods This is a cross-sectional study, which was done on 88 individuals of both genders (32 male and 56 female), over 18 years old with a mean age of 45 years old. These patients were referred by physicians after examination to our laboratories of Qaem Medical Laboratory of Kuhchenar and Jahrom University of Medical Sciences, Fars, Iran. The patients had recent symptoms and signs of hypothyroidism with increased TSH above the normal range, and negative serum anti-TPO antibody. To determine ABO, Rh, and Lewis (Le) blood groups was used anti-A, anti-B, anti-D, anti-Lea, and anti-Leb monoclonal antibodies. Serum T3, T4, and TSH was measured by direct chemiluminescent immunoassay. Anti-TPO antibody was measured by ELISA. CRP was determined using an immunoturbidimetric assay. CBC count assessment was done via an automated cell counter. Exclusion criteria were patients with acute or chronic inflammatory diseases. Herein, we evaluated the correlation of hematological parameters consisting ABO, Rh, and Le blood groups, RBC and WBC parameters, and platelet count as well as inflammatory biomarkers including ESR, CRP, IL-8, and NLR with T3, T4, and TSH in hypothyroid patients. Results Our study showed a significant correlation between Lea blood group (non-secretor) in comparison with Leb blood group (secretor) with TSH (P = 0.01). There was no correlation between Leb and Lea blood groups with T3 and T4. We did not observe the correlation between Rh and ABO blood groups with T3, T4, and TSH. We observed significant correlations between Hb, Hct, and MCH with T3 (PHb = 0.012, PHct = 0.021, and PMCH = 0.032) and also, with T4 in hypothyroidism (PHb = 0.023 and PHct = 0.026). We revealed significant correlations between Hb, Hct, and MCH with TSH in hypothyroidism (PHb = 0.017, PHct = 0.019, and PMCH = 0.007). The significant correlations between CRP and IL-8 with T3, T4, and TSH was not explored. The significant correlations between ESR with T3 and TSH was not detected. ESR showed a significant correlation with T4 (PESR = 0.020). There were also no significant correlations between the counts of neutrophils, lymphocytes, monocytes, and eosinophils, as well as NLR with T4. There was only significant correlation between monocyte count with T3 (PMono = 0.029) and also lymphocyte count with TSH (PLymph = 0.041). Conclusion In this investigation, we observed a significant relationship between Lea blood group in comparison with Leb blood group with TSH. We demonstrated significant correlations between Hb and Hct with T3, T4, and TSH, and also correlations between MCH with T3 and TSH. In conclusion, the assessment of Hb, Hct, MCH, and Le blood groups as hematological parameters can help physicians in the management of hypothyroidism.